CLINICAL-LABORATORY EVALUATION PROVISORY PASTE THE TREATMENT OF CHRONIC APICAL PERIODONTITIS - V. A. Ivashchenko; A. A. Adamchik (Кубанский научный медицинский вестник)
This article discusses the various aspects of bacterial contamination before and after treatment of chronic periodontitis and the choice of drug for the temporary investment of the root canal. As a result of the study revealed the presence of a bacterial pathogen in the root canal at the time of filling a permanent, that is a risk factor for apical periodontitis. Analysis of radiological and microbiological data for 24 months, lead to the conclusion that the paste for the temporary filling of root canal for the treatment of chronic apical periodontitis of the components calcium hydroxide, ciprofloxacin, minocycline, metronidozol, mixed with 2% chlorhexidine solution bigluconate well tolerated It has no side effects and contraindications. The data obtained allow to recommend the proposed paste for effective treatment of destructive forms of chronic periodontitis.